Implementation of a 3D virtual environment at the National University of the North West of the Province of Buenos Aires - Ramón, Hugo Dionisio (2013)
The increasing incorporation of ICTs in education is generating a series of changes and transformations in the ways we represent and carry out teaching and learning processes. These changes can be seen in the traditional environments of formal education but also in the arrival of new educational environments totally or partially based on ITCs. This document discusses the design, creation and coordination of a 3D virtual teaching and learning environment for UNNOBA. With that aim, the definition and deployment of a 3D virtual environment [3DVE] focuses not only on technological and pedagogical aspects but also on a transition methodology to improve the quality of teaching methods and techniques.